The Influence of Javanese Culture-Based Moral Education on Adolescent Behavior in Kediri - Widyasmoro, Hari (Journal of Education and Religious Studies, 2023)
This study examined the influence of Javanese culture-based moral education on adolescent behavior in Kediri. Using a qualitative approach, data were collected through interviews, observations, and questionnaires involving adolescents aged 13 to 18 years. The results revealed that values such as mutual cooperation, respect for elders, and simplicity were well internalized by teenagers and reflected in their daily behavior. The study also found that Javanese culture-based moral education effectively shaped responsible and ethical adolescent character, although modernization posed challenges that created tensions between traditional values and global influences. The implications of this study emphasized the importance of integrating cultural values into the education curriculum while adapting to the impact of modernization. Further study is recommended to explore how cultural values can be adapted in the context of globalization and to develop holistic educational strategies. These findings provided valuable insights for the advancement of culture-based character education in Kediri and other regions in Indonesia.